Pengembangan Booklet Famili Malvaceae sebagai Sumber Belajar Mata Kuliah Taksonomi Tumbuhan - Hamid, Muliana Gunawan (Journal of Science and Education Research, 2025)
This study aims to develop a booklet on the Malvaceae family as a learning resource for the Plant Taxonomy course. The method used is development research adapted from Thiagarajan's 4-D model, involving three stages: define, design, and develop, without the disseminate stage. The results showed that the Malvaceae family booklet is feasible to be used as a learning resource. The content feasibility aspect obtained a score of 4.63 (categorized as very valid), the language aspect scored 4.75 (very valid), the presentation aspect scored 4.67 (very valid), and the graphical aspect scored 4.63 (very valid). Thus, the booklet is considered suitable to support learning in the Plant Taxonomy course.